Modelling of commodity flows of drugstore chains using system dynamics tools - Левченко, Вадим Олегович (Technology audit and production reserves, 2015)
The modern tools of modeling commodity flows of pharmaceutical market are researched. The expediency of using system-dynamic modeling to control commodity flow of drugstore chains is proved. Simulation-system-dynamic model of commodity flows of drugs under uncertainty of demand, which includes submodel of commodity flows and submodel of logistics costs account, is developed and software implemented environment in Powersim Studio. The model allows for simulation of experiments to identify the impact of input and intermediate variables on the resulting indicators and tracking variables at each step of the simulation. It can be used in the same pharmacy or cover the commodity flows of the entire network and serves as a basis of the development process and making optimal decisions on inventory management in the drugstore chains. The results of practical testing of system-dynamic model of management of commodity flows in the practice of drugstore chains prove its effectiveness in terms of better meet demand and reduce logistics costs. Difficulties in using the model is the need to conduct multiple experiments with subsequent processing and integrating the results of simulation, the need for qualified personnel who will implement it and create adequate and effective solutions to manage commodity flow in the drugstore chain.